Preference for Sago and nutrient intake among communities consuming Sago in Kepulauan Meranti District, Riau Province, Indonesia - Syartiwidya, Syartiwidya; Martianto, Drajat; Sulaeman, Ahmad; Tanziha, Ikeu; Rimbawan, Rimbawan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This study aimed to analyse the preference for sago products and nutritional intake of the community consuming sago in Kepulauan Meranti District, Riau Province. A cross-sectional study was conducted and 181 adults was purposively selected subjects in Tebing Tinggi Timur Sub-district, Kepulauan Meranti District, Riau Province. The data obtained were subject characteristics, anthropometry, preferences for sago products, and nutritional intake from semi-quatitative food frequency questionnaire and food recall. The most preferred sago products out of 10 types of processed sago products were sago noodles (89.9%), sago lempeng (86.9%), and lemak sago (85.4%). Sago consumption frequencies among the subjects were mostly ‘often’ (39.2%) and ‘quite often’ (30.6%). The average amount of sago consumption was 173.7±88.3 g/day. The subject's average daily energy intake was 1864±468 kcal and the average protein intake was 48.4±21.7 g. The energy adequacy levels of subjects who consumed sago <140 g/day and ≥140 g/day were categorized as ‘normal’ (25.9% and 34.0% respectively). Meanwhile, the average level of protein adequacy were categorized as deficit (38.3% and 43.0% respectively). The carbohydrate adequacy levels were categorized as ‘excessive’ (80.2% and 71.0% respectively). The fat adequacy levels were categorized as ‘excessive’ (90.1% and 92.0% respectively). Sago noodles and lemak sago are two potential sago products to be developed as alternative carbohydrate sources due to their high frequency and preferability.